Debt financing determinants of Sharīʿah approved firms in Malaysia: evidence across industries - Ramli, Nurshamimitul Ezza; Haron, Razali (IIUM Institute of Islamic Banking and Finance, 2019)
Prior literature recorded a number of factors that determine debt level of the firms and these include firm’s specific determinants, industry determinants as well as economic determinants. However, very limited study explores in depth the roles of industry in determining firm’s debt level, especially in the Malaysian context. This study, therefore, explores further this issue by conducting across industry analysis to determine the effect of industry type in firm’s capital structure decision. Seven industries were selected i.e. construction, consumer, industrial, plantation, property, technology and trading and services. Uniquely, this study extends the analysis to the Sharīʿah approved firms perspective and covers a balanced panel of 239 Sharīʿah approved listed firms on Bursa Malaysia for the period from 2000 to 2014. Using the fixed effect model (FEM), the result shows inconsistency of determinants in determining the debt level of Sharīʿah approved firms in Malaysia across industries. However, strong evidence was found to conclude that size of the firms and bankruptcy risk react similarly to the debt level of all industries. This study provides new insight on the debt determinants of Sharīʿah approved firms in Malaysia as well as the effect of industry type in determining the debt level of the firms. This study also largely contributes in terms of the sampling selection in which a firm must be consistently being Sharīʿah approved during the period of analysis.